2015
DOI: 10.1007/s10433-015-0347-y
|View full text |Cite
|
Sign up to set email alerts
|

Social networks and mental health among older Europeans: are there age effects?

Abstract: This study examined different components of personal social networks-structure, interaction, and quality-and the extent to which each is related to mental health among a 65+ sample ( = 26,784) taken from the fourth wave of the Survey of Health, Ageing, and Retirement in Europe. The first aim of the study was to determine which network components had the strongest associations with the number of depressive symptoms, measured on the EURO-D scale. Secondly, the study considered if and how age impacted the associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 32 publications
2
29
0
1
Order By: Relevance
“…The positive effect of networks of family and friends on satisfaction with life of older adults has been shown by many previous studies [1, 4, 5, 810, 20, 29, 63]. However, certain characteristics of the social network, like the size and composition, and the satisfaction with life may be codetermined (i.e., while a larger and consolidated network may increase satisfaction with life, people with higher life satisfaction may be more extravert and able to develop a wider and diverse social network) and therefore an endogenous relationship may be present.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The positive effect of networks of family and friends on satisfaction with life of older adults has been shown by many previous studies [1, 4, 5, 810, 20, 29, 63]. However, certain characteristics of the social network, like the size and composition, and the satisfaction with life may be codetermined (i.e., while a larger and consolidated network may increase satisfaction with life, people with higher life satisfaction may be more extravert and able to develop a wider and diverse social network) and therefore an endogenous relationship may be present.…”
Section: Discussionmentioning
confidence: 74%
“…Burt also found that happiness is increased with the size of the discussion network [11] and Baldassare et al reached to similar conclusions using an elderly sample of respondents [12]. Social support, social interactions and the size of the social network have also been linked to other domains of well-being such as the general health status [1320], mortality [2127] and mental health [28, 29]. In fact, such links seem logical as Diener and Suh show that that there is a high correlation between life satisfaction and a social index that includes cost of living, ecology, health, culture and entertainment, freedom and infrastructure indicators [30].…”
Section: Introductionmentioning
confidence: 83%
“…Previous research has shown that healthy and “successful” ageing is determined in part by social embeddedness and social contact levels (Litwin et al 2015 ; Sirven and Debrand 2008 ). But because of ongoing demographic processes like higher childlessness rates and the trend towards smaller families, the number of close family members with whom older people can interact socially has declined (Frejka 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…While our study provides a number of interesting insights, it also has some limitations. The social contact frequency levels of older people may be influenced by the characteristics of the members of their social networks (Litwin et al 2015 ). Unfortunately, the socio-demographic characteristics of all the individuals in the social environment of the older people are not included in our data.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found, for instance, that the nature of the association between social network and wellbeing varies among people as a function of illness or disability ( e.g. Litwin, Stoeckel and Schwartz 2015). In addition, frequency of contact with the social network is positively associated with various wellbeing outcome measures among well older adults, but not necessarily associated (or even negatively associated) among older adults with disability (Litwin and Stoeckel 2013 a , 2013 b ).…”
Section: Literature Reviewmentioning
confidence: 99%